2019
DOI: 10.1002/jcb.28726
|View full text |Cite
|
Sign up to set email alerts
|

The expression of long non coding RNA genes is associated with expression with polymorphisms of HULC rs7763881 and MALAT1 rs619586 in hepatocellular carcinoma and HBV Egyptian patients

Abstract: Long noncoding RNAs (lncRNAs), highly upregulated liver cancer (HULC), metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1), lncRNA‐AF085935, and lncRNA‐uc003wbd have been implicated in hepatocellular carcinoma (HCC). Single‐nucleotide polymorphism (SNP) in HULC and MALAT1 are associated with HCC susceptibility. However, association between these SNPs and lncRNA‐AF085935 and lncRNA‐uc003wbd expression and their potential clinical value in differentiating HCC from both hepatitis B virus (HBV)‐infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…In recent years, a number of studies have reported the association of lncRNA HULC polymorphisms with decreased risk of HCC, ESCC, and CRC. [24][25][26][27] In this casecontrol study, we first investigated the association between HULC rs7763881 SNP and GC risk but did not observe a significant association between them. However, stratified analysis by age, gender, tumor differentiation, histological type, LNM, T classification, and tumor stage revealed statistically significant association between HULC rs7763881 CC genotype and increased GC risk of the undifferentiated, diffuse-type, LNM-positive, T3/T4, and tumor stage III groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a number of studies have reported the association of lncRNA HULC polymorphisms with decreased risk of HCC, ESCC, and CRC. [24][25][26][27] In this casecontrol study, we first investigated the association between HULC rs7763881 SNP and GC risk but did not observe a significant association between them. However, stratified analysis by age, gender, tumor differentiation, histological type, LNM, T classification, and tumor stage revealed statistically significant association between HULC rs7763881 CC genotype and increased GC risk of the undifferentiated, diffuse-type, LNM-positive, T3/T4, and tumor stage III groups.…”
Section: Discussionmentioning
confidence: 99%
“…Till date, contradictory to our results, previous studies have reported the relationship between rs7763881 AC or AC+CC genotype with the decreased risk of several cancers, including HBV carried HCC, ESCC, and CRC. [24][25][26][27] Through stratification analysis. Of Chinese populations, Kang between HOTAIR overexpression and poor differentiation, LNM, and advanced tumor stage (III-IV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the selection criteria, 12 studies [17][18][19][20][21][25][26][27][28][29][30][31] were included in this meta-analysis ( Fig. 1).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Recent advancements in high-throughput gene sequencing analysis have led to the identification of a large number of differentially expressed long non-coding RNAs (lncRNAs) in the progression of various cancers (Jing et al, 2018;Li et al, 2018;Malih, Saidijam & Malih, 2016). A growing number of studies have reported that dysregulated lncRNAs in HCC are related to chronic HBV or HCV infection, histological type, TNM stage, lymph node metastasis, and prognosis Motawi et al, 2019;Zheng et al, 2017). Closely related dysregulated lncRNAs may assist in identifying valuable biomarkers for the diagnosis and prognosis of HCC.…”
Section: Introductionmentioning
confidence: 99%